Exploring TESOL Pedagogies in Japan: An Autoethnographic Study of Eikaiwa Teaching Practices - San Jose, Dominic Bryan; Guitche, Melona (Cultural Arts Research and Development, 2025)
With eikaiwa (English conversation schools) playing a crucial role in Japan’s English education landscape, the pedagogical methods used in eikaiwa have received relatively little attention. Thus, utilizing the three-dimensional framework of temporality, sociality, and spatiality, this autoethnographic study explored and documented the teaching practices used and adopted by one of the researchers as a TESOL teacher at eikaiwa schools in Japan. The findings reveal a transition from grammar-focused instruction to student-centered, interactive approaches, influenced by communicative language teaching, task-based learning, and translanguaging strategies. It concludes that factors like social dynamics, institutional constraints, and physical environments shape teaching practices and dynamics in eikaiwa settings. These factors influence teachers to either withdraw or transition from the dominance of grammatical formalism to more student-centered, responsive, and contextualized approaches to learning, as demonstrated by the participant. Moreover, the study points out how the commercial environment in eikaiwa often leads to a conflict between educational purpose and commercial gain but believes that these types of constraints can be the ones that can also drive pedagogical innovations. Lastly, it highlights the role of spatial design in improving classroom and learning interactions that may be relevant beyond eikaiwa settings. While findings may be applicable beyond eikaiwa settings, the study acknowledges its limitations in terms of generalizability across Japan’s eikaiwa institutions. Further studies are needed to shed light on the overall circumstances of eikaiwa teachers in Japan. Implications suggest the need for greater pedagogical autonomy and professional development in private language teaching settings.